Performance, quality an in vitro biogas in grass Megathyrsus maximus cv. Aruana with different fertilization - Sánchez-Santillán, Paulino; Wilson-García, Claudia Yanet; López-Zerón, Nelson Erick; Saavedra-Jiménez, Luis Antonio; Maldonado-Peralta, María de los Ángeles; Melo-Trani, Mara Yuciry (Ecosistemas y Recursos Agropecuarios, 2021)
The objective was to evaluate the yield, bromatological composition and biogas production in vitro with organic and inorganic fertilization, to determine the optimal cutting age of Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs cv. aruana. The treatments were; fertilization with compost, vermicompost, compost plus leachate and chemical fertilization. The experimental design was complete randomized blocks, in an arrangement of measures repeated in time with three repetitions, samplings were carried out at 20, 35, 50, 65, 80 and95 days after the cut-off (DDC) of standardization. The variables evaluated were accumulation of dry matter, morphological composition, height, neutral detergent fiber, acid detergent fiber, organic matter, crude protein, ash, and in vitro biogas production. The highest yields were at 80 DDC with the chemical treatments and the most leached compost with 24 013 and 10 974 kg DM ha-1, respectively. In the organic treatments, a higher leaf: stem ratio was found compared to the chemical one in all the evaluated dates. The treatments showed a decrease in the percentage of crude protein as the regrowth age advanced. At 50 and 95 DDC, the aruana grass fertilized with vermicompost or more leached compost produced  2.8 and 2.0 times more biogas than the one fertilized with chemical or compost. The optimal cutting date for aruana grass for the most leached chemical treatment and compost is 50 and 65 DDC, while for vermicompost and compost it is 65 DDC.